Neurocognitive impairment in childhood chronic fatigue syndrome - Mizuno, Kei; Watanabe, Yasuyoshi (Frontiers in Physiology, 2013)
Neurocognitive impairment is a feature of childhood chronic fatigue syndrome (CCFS). Several studies have demonstrated reduced attention control in CCFS patients in switching and divided attention tasks. In students, the extent of deterioration in task performance depends on the level of fatigue. Poor performance in switching and divided attention is common in both fatigued students and CCFS patients. Additionally, attentional functions show dramatic development from childhood to adolescence, suggesting that abnormal development of switching and divided attention may be induced by chronic fatigue. The brain structures associated with attentional control are situated in the frontal and parietal cortices, which are the last to mature, suggesting that severe fatigue in CCFS patients and students may inhibit normal structural and functional development in these regions. A combination of treatment with cognitive behavioral therapy and antidepressant medication is effective to improve attentional control processing in CCFS patients. Studies identifying the features of neurocognitive impairment in CCFS have improved our current understanding of the neurophysiological mechanisms of CCFS.